2022
DOI: 10.1177/20406207221132346
|View full text |Cite
|
Sign up to set email alerts
|

Serum proteomics screening intercellular adhesion molecule-2 improves intermediate-risk stratification in acute myeloid leukemia

Abstract: Background: The clinical risk classification of acute myelocytic leukemia (AML) is largely based on cytogenetic and molecular genetic detection. However, the optimal treatment for intermediate-risk AML patients remains uncertain. Further refinement and improvement of prognostic stratification are therefore necessary. Objectives: The aim of this study was to identify serum protein biomarkers to refine risk stratification in AML patients. Design: This study is a retrospective study. Methods: Label-free proteomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…ICAM2, a transmembrane glycoprotein of the immunoglobulin superfamily, regulates immune responses and contributes to the occurrence of some cancers [ 32 ]. Recent studies have reported that ICAM2 is deregulated in multiple human cancers [ 33 ]. However, whether ICAM2 plays a role in GC development remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…ICAM2, a transmembrane glycoprotein of the immunoglobulin superfamily, regulates immune responses and contributes to the occurrence of some cancers [ 32 ]. Recent studies have reported that ICAM2 is deregulated in multiple human cancers [ 33 ]. However, whether ICAM2 plays a role in GC development remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [ 99 ]. used label-free quantitative proteomics in profiling the proteome of 10 BM plasma samples of newly diagnosed AML and 3 healthy donors.…”
Section: Omics In Diagnosis Of Amlmentioning
confidence: 99%
“…One of the first promoters shown to achieve uniform, high-level transgene expression in the vasculature of transgenic mice was that of the human intercellular adhesion molecule 2 gene (ICAM-2). This is a proteomic marker used until now to determine the aging phenomena that occur at the liver, acute myeloid leukemia, and lung levels [ 19 ]. In humans, this marker is a counter receptor for lymphocyte function-associated antigen-1 and can provide a costimulatory signal for T cell stimulation through the allogeneic major histocompatibility complex class II.…”
Section: Introductionmentioning
confidence: 99%